Empirical formulas for determining the characteristic parameters of the eutectics in quasibinary cermet systems - Zakarian, D.A.; Kartuzov, V.V.; Khachatrian, A.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
For quasibinary boride and cermet systems, the calculation-empirical formula are obtained to determine the concentration and the temperature at an eutectic point, depending on the temperature difference between the melting components based on the results of computer simulation from the first principles.